(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Food safety remains a critical global public health concern, particularly with widely consumed products like edible oil. In Nigeria, groundnut oil is a dietary staple, produced on scales ranging from small enterprises to large industries and also imported. However, its safety often receives limited attention. This study evaluated fungal contamination and aflatoxin B1 (AFB1) levels in groundnut oil samples from markets in Kaduna Metropolis. Twenty (20) composite samples were randomly collected from five locations. Standard mycological methods were used for fungal isolation, while AFB1 quantification was performed using Enzyme-Linked Immunosorbent Assay (ELISA). Four fungal genera of Aspergillus, Mucor, Fusarium, and Rhizopus spp. were identified. The highest fungal load (9.5 10 CFU/mL) was found in Central Market samples, while the lowest (2.1 10 CFU/mL) was from Gonin-Gora Market. Fungal prevalence was 20% across all genera, except Fusarium spp. (10%). One-way ANOVA indicated significant differences in fungal loads between locations (P 0.05). AFB1 was detected in all samples, with highest concentrations from Gonin-Gora (5.8 g/mL) and Central Market (4.6 g/mL), both exceeding the European Unions permissible limit of 4.00 g/mL. Other samples remained within acceptable safety thresholds. AFB1 levels also varied significantly by location (P 0.05), likely influenced by environmental and handling factors. The presence of AFB1 above regulatory limits highlights potential health risks associated with prolonged consumption. Thus, routine monitoring and vendor education on hygienic practices in oil packaging and storage are essential to reduce fungal growth and toxin production.